Converting the Function of Rubber to Palm Oil Plantation to Improve the Economy of the Community in Kampung Dalam Village District of Bilah Hulu, District of Labuhanbatu - Budi Santoso; Widya Lestari; Khairul Rizal; Fitra Syawal Harahap (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the physical properties of land conversion from rubber land to coconut plantations (cocos nucifera L) in Kampung Dalam Village, Bilah Hulu District, Labuhanbatu Regency. Soil analysis was carried out at the Agricultural Soil Clinic, Agricultural, Fisheries, Forestry Extension Commission (KP3K) Deli Serdang Regency, North Sumatra Province. The method used in this research is a field survey by reviewing and determining the location and determining the location of observation points on the conversion of rubber land to coconut plantations and continuing to take soil samples as material for analysis in the laboratory. Soil sampling with a ring sample with a depth of (20 cm) from the top soil layer. In the land conversion of rubber land into coconut plantations, 4 soil samples were taken with a distance of 100 meters in the field with a random method spread over a predetermined area based on a base map. Parameters analyzed in this study include Bulk Density, Total Pore Space, Field Capacity, Withering Point, Soil Texture. The results showed that the density of the soil mass was 0.17 g.cmֿ³, the total pore space was 45.56 %, the field capacity (%) was 252.07%, the lay point (%) was 252.07%, and the character of the soil at the study site was entered in clay character.